KH. ABDULLAH SYFI'IE BIN SYFI'IE BIN SAIRAN'S COMMUNITY DEVELOPMENT EFFORTS THROUGH DA'WAH - Sirojuddin Sirojuddin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
In theory, Da'wah is the process of applying Islamic teachings to foster a positive society. From a scholarly perspective, Da'wah science can be categorized into two distinct parts: basic and applied Da'wah science. Basic Da'wah science delves into the theoretical and foundational aspects of Da'wah, while applied Da'wah science focuses on its practical implementation. In the context of applied Da'wah science, one effective approach to comprehending the practical aspects of Da'wah is to study the rules and methodologies of Da'wah found in the Quran and Hadith, particularly those employed by Prophets and Messengers. Additionally, these principles of Da'wah implementation can be gleaned from the teachings and practices of revered Islamic figures and scholars. Among the distinguished figures in the realm of Da'wah is K.H. Abdullah Syafi'ie bin Syafi'ie bin Sairan, a charismatic Betawi cleric known for his profound knowledge. This study revolves around three main focal points: Firstly, it explores the unique qualities and charisma that set KH Abdullah Syafi'ie bin Syafi'ie bin Sairan apart as an accomplished Da'i from the Betawi community. Secondly, it delves into the specific Da'wah approach employed by KH Abdullah Syafi'ie bin Syafi'ie bin Sairan, which left a lasting impact on the Islamic community in Betawi. Thirdly, it examines the practical manifestations of KH Abdullah Syafi'ie bin Syafi'ie bin Sairan's ideas in the development of the Betawi Islamic Community. The theoretical underpinning of this study rests on two key concepts: First, it draws inspiration from the community development model of the Prophet Muhammad's era, notably the Medina Charter, as an exemplar of community-building in an Islamic context. Second, it incorporates the contemporary perspective of community development as articulated by Brokensha and Hodge, who define it as a movement aimed at enhancing the overall quality of life for an entire community through active participation. This research adopts a qualitative approach, primarily employing qualitative descriptive research methods. Following the research planning phase, the author conducts fieldwork, which includes direct observations, informant interviews, and data collection pertaining to the subject of research. The findings of this study underscore that KH Abdullah Syafi'ie effectively propagated his ideas through various means, including oral communication, written materials, practical actions, political engagement, and the use of electronic media such as radio. These multifaceted approaches collectively contributed to a transformation in the societal fabric, aligning it more closely with the ideals espoused in the Quran and Hadith, as desired by Allah and the Prophet.